Understanding Barriers and Facilitators to Healthy Eating and Active Living in Rural Communities. (10th December 2014) - Seguin, Rebecca; Connor, Leah; Nelson, Miriam; LaCroix, Andrea; Eldridge, Galen
Abstract : Objective . Studies demonstrate that people's food and physical activity (PA) environments influence behavior, yet research examining this in rural communities is limited. Methods . Focus groups of 8–15 women were conducted in rural communities in seven US states. Questions were designed to identify factors within residents' food and PA environments they felt helped or hindered them from eating healthfully and being physically active. Results . Participants were aged 30–84 years; mean (SD) = 61 (14) (N = 95 ). On average, communities had fewer than 5, 000 residents. Limited time, social norms, and distances from or lack of exercise facilities were common PA barriers. Facilitators for PA included social support, dog walking, and availability of affordable facilities. Healthy eating barriers included the perception that healthy foods were too expensive; calorically dense large portion sizes served at family meals; and frequency of eating foods away from home, which were perceived as generally unhealthy. Healthy eating supports included culture/value around local food gathering (e.g., hunting and gardening) and preservation (e.g., canning and smoking). Friends and family were frequently identified as key influencers of eating and PA behavior. Conclusions . Targeting both social and built environment factors, particularly those unique to rural locales, may enhance support for healthy eating and PA behavior change interventions.